2014
DOI: 10.5545/sv-jme.2014.1698
|View full text |Cite
|
Sign up to set email alerts
|

An Enhanced Control Technique for the Elimination of Residual Vibrations in Flexible-Joint Manipulators

Abstract: One method used to reduce or eliminate residual vibrations is to modify the input signal by using previously determined system parameters. In order to eliminate the residual vibration completely, these system parameters must be very accurately determined. In real systems, achieving such accuracy may not always be possible. To address this problem and to provide a solution, a new residual vibration elimination method is introduced in this study, which has proven to be useful especially in cases of uncertain par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 26 publications
(30 reference statements)
0
6
0
Order By: Relevance
“…Because the first step is completed with almost steady motion and with relatively reduced vibration levels, the second part of the motions starts with the advantage of very little or almost no residual vibrations. As a result of the second part of the motion yields better performance to the CPRVPR method [26].…”
Section: Modified Cycloid Plus Ramped Versine Plus Ramp (M-cprvpr) Rementioning
confidence: 99%
See 2 more Smart Citations
“…Because the first step is completed with almost steady motion and with relatively reduced vibration levels, the second part of the motions starts with the advantage of very little or almost no residual vibrations. As a result of the second part of the motion yields better performance to the CPRVPR method [26].…”
Section: Modified Cycloid Plus Ramped Versine Plus Ramp (M-cprvpr) Rementioning
confidence: 99%
“…The calculations for the method are as follows where the input is divided into two sections and each one is calculated independently to form the first and the second part of the input signal. A motion profile of a modified CPRVPR function is described by Conker et al [26]:…”
Section: Modified Cycloid Plus Ramped Versine Plus Ramp (M-cprvpr) Rementioning
confidence: 99%
See 1 more Smart Citation
“…They have indicated that their approach is far more robust at high frequencies. Conker et al 18 proposed a control technique developed by the hybrid input shaping method to remove the residual vibrations in flexible link robotic systems. Mar et al 19 developed a control system that combines input shaping and feedback control for double-pendulum systems exposed to external disturbance.…”
Section: Introductionmentioning
confidence: 99%
“…The performance of a robotic manipulator is characterized by a well-defined control approach [2]. Classical or trivial control strategies are usually based on linear control laws while modern approaches are nonlinear in nature.…”
Section: Introductionmentioning
confidence: 99%